Comparative Assessment of Morphometry, Morphology, and Maturation Capacity of Vitrified Cattle Oocytes in Different Media - Maleke Dimpho Sebopela; Ntuthuko Raphael Mkhize; Mamonene Angelinah Thema; Masindi Lottus Mphaphathi (Veterinary Sciences)
This study aimed to compare the morphometry, morphology, and maturation capacity of cattle oocytes subjected to vitrification using different vitrification and maturation media. In Experiment 1, a total of 900 oocytes were divided into three groups: (1) matured before vitrification, (2) non-vitrified, and (3) vitrified as immature oocytes using the straw vitrification method. Morphometric parameters, including oocyte diameter, ooplasm, zona pellucida width (ZPW), granulosa cell width (GRSW), and zona pellucida-granulosa cell width (ZP GRSW), were measured (µm) before and after cryopreservation. In Experiment 2, the maturation capacity of three in vitro maturation (IVM) media (VitroMat-Protect™, BO-IVM™, and TCM199) was evaluated based on cumulus–oocyte complex (COC) expansion and polar body (PB) extrusion. Morphological abnormalities such as fragmented polar bodies (FPBs), large vacuoles (LVs), degenerated oocytes (DOs), and cracked cytoplasm (CC) were recorded. While vitrification did not significantly affect the oocyte diameter, ooplasm, or ZPW, it significantly reduced the GRSW and ZP GRSW. BO-IVM™ supported the highest COC expansion rate, while TCM199 had the lowest. Among vitrified oocytes, the highest PB extrusion rates were observed in BO-IVMTM (35.14 ± 5.01) and Vitromat-ProtectTM (24.60 ± 5.67) as compared to TCM199 (18.44 ± 8.00; p < 0.05). Oocytes with higher CC rates were observed in VitroMat-Protect™ (24.50 ± 10.53) and BO-IVM™ (31.42 ± 7.32) as compared to TCM199 (18.70 ± 7.04). In conclusion, the vitrification process affects the granulosa cells in both vitrified immature and mature oocytes. BO-IVMTM and VitroMat-ProtectTM supported better oocyte maturation than TCM199, although vitrification increased FPB and CC rates.